Molecular Diagnostics for Melanoma Methods and Protocols - Thurin, Magdalena.; Thurin, Magdalena.; Marincola, Francesco M.; Marincola, Francesco M. (Methods in Molecular Biology,, 2014)
In Molecular Diagnostics for Melanoma: Methods and Protocols, expert researchers and clinicians in the field of melanoma provide updated information on biomarkers and assays for diagnosis, prognosis, and assays predicting response to treatment for routine testing. The focus of the volume is on biomarkers with established clinical validity rather than those on early discovery stage.  With additional in-depth discussion of the molecular biology and pathology of melanoma, treatment options in adjuvant and metastatic setting, and implications of biomarker testing for clinical management of melanoma patients.   Written in the highly successful Methods in Molecular Biology series format, chapters include extensive introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and key tips on troubleshooting and avoiding known pitfalls.   Comprehensive and practical, Molecular Diagnostics for Melanoma: Methods and Protocols seeks to provide both clinicians and scientists with technical information and extensive background information on the wide ranging approaches available in the field of diagnostics of melanoma.